Kajian Parkir Badan Jalan pada Kawasan Perbelanjaan (Studi Kasus: Jalan Pemuda, Pecinan Magelang) - Puspitasari, Evi; Maryunani, Woro Partini; Hutomo, Paska Adi (Department of Civil Engineering, Diponegoro University, 2020)
The economic growth has influenced the mobility of the population. In line with those, there is a rapid growth of private vehicle ownership. The growth of private vehicles must be fulfilled by enough parking space so that it doesn’t cause parking problems later. This study aims to describe the conditions and evaluate the existing parking management in the case study area and design an effective parking space scenario. The object of this research is the on-street parking area on shopping area, Pemuda Street, Chinatown, Magelang. To obtain an overview of parking management in case study area, several surveys were conducted, including a parking inventory survey, occupancy survey, and parking duration survey. Secondary data collected by interview with the Local Transportation Department and the Local Public Works and Spatial Planning Department. The survey results show that existing parking requirements cannot be met by the existing parking area. However, the traffic conditions around the Chinatown have not shown congestion during peak hour. To further improve the effectiveness of parking management in Chinatown, parallel parking, parking meter implementation, the addition of parking space and the application of parking based on duration can be applied. For further research, research on parking using special transportation software can be done.